Joint effect of overweight/obesity and tobacco exposure on hypertension in children aged 6–17 years: a cross-sectional study - Gu, Huan; Hao, Long; Li, Mingxi; Li, Ji (Frontiers in Pediatrics, 2023)
Aim: To assess the individual effects of overweight/obesity and tobacco exposure, and their combined effects on hypertension in children. Methods: This cross-sectional study included 6,339 children aged 6-17 years from National Health and Nutrition Examination Surveys 1999-2018. Participants’ height, weight and blood pressure (BP) were measured by trained technicians. Hypertension was defined as: mean systolic BP (SBP) and/or diastolic BP (DBP) ≥90th percentile for sex, age, and height (for children aged 1-13 years), and SBP ≥120 mmHg and/or a DBP ≥80 mmHg (for adolescents aged 13-17 years); or self-reported having been diagnosed with hypertension or taking antihypertensive medication. Gender- and age-specific body mass index (BMI) cut-points were used to define overweight/obesity: “overweight” was defined as a BMI>1 standard deviation (SD); “obesity” was defined as BMI>2SD; and “thinness” was defined as BMI<-2SD. Tobacco exposure was defined as having serum cotinine levels >0.05µg/L or reporting the presence of at least one smoker in the household. Weighted univariate and multivariate logistic regression models were used to assess overweight/obesity and tobacco exposure with the odds of hypertension, and the combined effects of overweight/ obesity and tobacco exposure on hypertension, followed by strata-specific analyses. Odds ratios (OR) with 95% confidence intervals (CI) were calculated. Results: The prevalence of overweight/obesity and tobacco exposure was significantly higher in the hypertension group than in the non-hypertension group. Overweight/obesity (OR=1.67, 95%CI: 1.26-2.21/ OR=2.38, 95%CI: 1.67-3.39) and tobacco exposure (OR=1.58, 95%CI: 1.16-2.14) were associated with a higher odd of hypertension in children, respectively. Additionally, we also observed the combined effect between overweight (OR=3.05, 95%CI: 1.96-4.75)/obesity (OR=3.68, 95%CI: 2.24-6.03) and tobacco exposure were related to hypertension odds in children, with a significant effect in different populations. Conclusion: There may exist joint effect of overweight/obesity and tobacco exposure on the odds of hypertension in American children. These findings offer an insight that early weight control and reduction of tobacco exposure may be important to reduce odds of hypertension in children.